From neuromodulation to bone homeostasis: therapeutic targets of nerve growth factor in skeletal diseases - Chen, Kaixuan; Chen, Longjun; Ma, Yizhong; Chen, Siqi; Liu, Jinze; Zhou, Hangyu; Chen, Yuzhu; Liu, Guanyi (Frontiers in Pharmacology, 2025)
The skeletal system is an important support structure in the human body, and its homeostatic state is highly relevant to the development of a wide range of orthopaedic diseases. The search for key regulatory factors associated with skeletal development is essential for exploring potential therapeutic targets for bone diseases. Nerve Growth Factor (NGF), the first neurotrophic factor to be discovered, plays an important role in regulating immune cell function, influencing angiogenesis and participating in the physiological and pathological processes of bone homeostasis. Here, we mainly review the biological functions of NGF in the skeletal system and its molecular mechanisms, analyse the pathophysiological roles of the NGF signaling pathway in skeletal diseases such as osteoporosis, osteoarthritis, and fracture healing, and summarize the progress and challenges of the current clinical research on therapeutic strategies targeting NGF. In addition, we provide an overview of NGF and highlight the role of NGF in the regulation of bone formation and bone resorption. Therefore, by reviewing the literature related to NGF and bone diseases, this paper summarises the specific regulatory mechanisms of NGF in various bone diseases, which provides new perspectives and intervention targets for the treatment of skeletal diseases, especially in the field of diseases in which the effects of traditional treatments are limited. The therapeutic strategies targeting neurotrophic factors show broad prospects for clinical application.